Statue of Christopher Columbus, Port of Spain - Trinidad - (:unkn) unknown (Goodwille and Wilson Ltd., Trinidad, 2010)
This photograph of could have been taken circa 1900-1910. It gives a closer view of the statue of Christopher Columbus upon the top of the monument to Christopher Columbus: navigator; explorer; colonizer, who encountered Trinidad in 1498 on his third voyage, in Columbus Square, corner of Independence Square and Duncan Street, Port of Spain. The iron statute was a gift from Hippolyte Borde, an affluent local cacao planter and merchant and it stands at the top of a monolithic platform which has four gargoyles with open mouths, or spouts, and four basins beneath each. This arrangement then rests in a large round fountain which is railed around with chains and an iron fence. Many large trees including a Samaan surround the monument. What might be a light pole, with an intricately decorated wrought iron top is on the left of the photograph near the monument. There are buildings in the background.
Colour: Sepia; Style: Landscape; Other: Unbordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Monuments; Statues; Columbus, Christopher; Trees; 1907; 1907